2000
DOI: 10.4049/jimmunol.164.12.6303
|View full text |Cite
|
Sign up to set email alerts
|

Mice with a Selective Deletion of the CC Chemokine Receptors 5 or 2 Are Protected from Dextran Sodium Sulfate-Mediated Colitis: Lack of CC Chemokine Receptor 5 Expression Results in a NK1.1+ Lymphocyte-Associated Th2-Type Immune Response in the Intestine

Abstract: The chemokine receptors CCR2 and CCR5 and their respective ligands regulate leukocyte chemotaxis and activation. To determine the role of these chemokine receptors in the regulation of the intestinal immune response, we induced colitis in CCR2- and CCR5-deficient mice by continuous oral administration of dextran sodium sulfate (DSS). Both CCR2- and CCR5-deficient mice were susceptible to DSS-induced intestinal inflammation. The lack of CCR2 or CCR5 did not reduce the DSS-induced migration of macrophages into t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
152
2
2

Year Published

2002
2002
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(167 citation statements)
references
References 66 publications
11
152
2
2
Order By: Relevance
“…No significant differences were found between WT and CCR6-deficient mice in macrophage infiltrate in the inflamed mucosa, a feature of DSS-mediated colitis. A recent study reported that CCR2-or CCR5-deficient mice are protected from DSS-mediated colitis, despite the fact that these g -chemokine receptor-defective animals and the corresponding WT controls showed similar macrophage infiltrates in intestinal mucosa [36]. In our experiments, estimated CD4 mRNA levels in colon at day 0 and during the acute colitis phase indicated that there were more CD4 + and CD8 + T cells in CCR6-deficient than in WT mouse colons.…”
Section: Discussioncontrasting
confidence: 40%
See 1 more Smart Citation
“…No significant differences were found between WT and CCR6-deficient mice in macrophage infiltrate in the inflamed mucosa, a feature of DSS-mediated colitis. A recent study reported that CCR2-or CCR5-deficient mice are protected from DSS-mediated colitis, despite the fact that these g -chemokine receptor-defective animals and the corresponding WT controls showed similar macrophage infiltrates in intestinal mucosa [36]. In our experiments, estimated CD4 mRNA levels in colon at day 0 and during the acute colitis phase indicated that there were more CD4 + and CD8 + T cells in CCR6-deficient than in WT mouse colons.…”
Section: Discussioncontrasting
confidence: 40%
“…The origin of this increase in T cell transcript levels may be, at least in part, a consequence of altered lymphocyte homeostasis, which provokes a basal increment of those cells in the intestinal mucosa of CCR6-deficient mice [30,31]. Andres et al observed a similar increase in CD4 + /CD8 + T cells when analyzing colitis development in CCR5-deficient mice [36].…”
Section: Discussionmentioning
confidence: 95%
“…Notably, the induction of a Th1 response by macrophage derived dendritic cells can occur through the interaction between CCR5 and its ligand, independent of IL-12, indicating that chemokines alone can affect T cell differentiation [29]. Indeed, in mice lacking CCR5 there is a skewed Th2 cytokine profile, providing further confirmation that CCR5 is involved in determining T helper cell fate [30]. Viewed together, these data suggest that CCL5-CCR5 interactions are important not only in the initial recruitment of T cells to an inflammatory lesion, but also as determinants for the differentiation of Th1 T cells.…”
Section: Chemokines Influence T Cell Fatementioning
confidence: 88%
“…Individuals, who are homozygous for 32-bp deletion in the gene encoding CCR5, whilst otherwise healthy, are strongly protected against infection [2]. Many studies indicate different roles for CCR5 and its ligands in disorders such as rheumatoid arthritis [3], multiple sclerosis [4], transplant rejection [5] and inflammatory bowel disease [6]. These observations suggest that molecules that modulate the CCR5 receptor would have potential benefit in a wide range of diseases.…”
Section: Introductionmentioning
confidence: 99%